2009
DOI: 10.1002/cphc.200900067
|View full text |Cite
|
Sign up to set email alerts
|

Blue Luminescence Emitted from Monodisperse Thiolate‐Capped Au11 Clusters

Abstract: Gold clusters (Au n , n = the number of gold atoms in the core) containing less than 200 down to a few atoms have gained great attention in the last decade. [1][2][3][4][5][6][7][8] Because only a few gold atoms are contained in the clusters, the size of the clusters approaches the de Broglie wavelength of the conduction electrons. The density of states is insufficient to merge the valence and conduction bands, which allows discrete cluster energy levels to become possible. As a result, gold clusters are likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…In recent years, employing state-of-the-art quantum chemistry codes, relatively accurate prediction and explanation of the optical properties of a broad range of NCs have been realized [812]. A broad range of luminescent metal NCs composed of gold (Au) [57, 1327], silver (Ag) [12, 2536], copper (Cu) [25, 35, 37, 38], platinum (Pt) [25, 39, 40], bismuth (Bi) [11, 4145], molybdenum (Mo) [4648] or mixed metals [4951] have been successfully fabricated using diverse top-down or bottom-up approaches. Compared with other counterparts, Au and Ag NCs have attracted more attention and have been intensively studied over the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, employing state-of-the-art quantum chemistry codes, relatively accurate prediction and explanation of the optical properties of a broad range of NCs have been realized [812]. A broad range of luminescent metal NCs composed of gold (Au) [57, 1327], silver (Ag) [12, 2536], copper (Cu) [25, 35, 37, 38], platinum (Pt) [25, 39, 40], bismuth (Bi) [11, 4145], molybdenum (Mo) [4648] or mixed metals [4951] have been successfully fabricated using diverse top-down or bottom-up approaches. Compared with other counterparts, Au and Ag NCs have attracted more attention and have been intensively studied over the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…[43] However,some Au clusters with green or blue fluorescence have also been described. [44,[46][47][48][49][50] This discrepancy could be due to the fact that the emission wavelength of gold nanoclusters is influenced by multiple factors such as the protecting ligands [46,48] and the …”
mentioning
confidence: 99%
“…reported that dihydrolipoic acid protected gold nanoclusters displayed an emission maximum at 700 nm . However, some Au clusters with green or blue fluorescence have also been described . This discrepancy could be due to the fact that the emission wavelength of gold nanoclusters is influenced by multiple factors such as the protecting ligands and the nanocluster size .…”
Section: Figurementioning
confidence: 99%